The Assembly Switch Mechanism of FtsZ Filament Revealed by All-Atom Molecular Dynamics Simulations and Coarse-Grained Models - Lv, Dashuai; Li, Jingyuan; Ye, Sheng (Frontiers in Microbiology, 2021)
Bacterial cytoskeletal protein FtsZ binds and hydrolyzes GTP, and assembles into dynamic filaments that are essential for cell division. Here, we used a multi-scale computational strategy that combined all-atom molecular dynamics (MD) simulations and coarse-grained models to reveal the conformational dynamics of assembled FtsZ. We found that the top end of a filament is highly dynamic and can undergo T-to-R transitions in both GTP- and GDP-bound states. We observed several subcategories of nucleation related dimer species, which leading to a feasible nucleation pathway. In addition, we observed that FtsZ filament exhibits noticeable amounts of twisting, indicating a substantial helicity of the FtsZ filament. These results agree with the previously models and experimental data. Anisotropy network model (ANM) analysis revealed a polymerization enhanced assembly cooperativity, and indicated that the cooperative motions in FtsZ are encoded in the structure. Taken together, our study provides a molecular-level understanding of the diversity of the structural states of FtsZ and the relationships among polymerization, hydrolysis, and cooperative assembly, which should shed new light on the molecular basis of FtsZ’s cooperativity.